Efficient perovskite solar cells enabled by large dimensional structured hole transporting materials. Issue 3 (4th January 2021) - Wu, Tai; Zhang, Dongyang; Ou, Yangmei; Ma, Huili; Sun, Anxin; Zhao, Rongmei; Zhu, Liqiong; Wang, Runtao; Zhuang, Rongshan; Liu, Gaoyuan; Zhao, Yuanju; Lai, Qian; et al.
Abstract : A large dimensional structured hole transporting material exhibits excellent photovoltaic performance in perovskite solar cells. Abstract : The hole-transport material (HTM) in perovskite solar cells (PSCs) plays a critical role in achieving high photovoltaic performance and long-term stability. Although a great number of HTMs have been explored for perovskite solar cells (PSCs), only a few reported HTMs can comprehensively outperform the current state-of-the-art Spiro-OMeTAD . Moreover, further understanding of the relationship between the photovoltaic performance of PSCs and the chemical structure of HTMs is imperatively needed. In this work, two novel HTMs (YT4 and YT5 ) have been developed for application in PSCs and the influence of the different dimensional structures of the HTMs on the photovoltaic performance of the PSCs was also investigated accordingly. YT5 with a larger dimensional structure possesses a lower-lying HOMO energy level, a higher hole-extraction/transport ability and conductivity, and a better film morphology. Consequently, the hybrid PSCs based on YT5 exhibits a remarkable power conversion efficiency (PCE) of 21.34%, which is significantly higher than that of the cell employing YT4 (18.58%). Meanwhile, YT5 can also be applied in all-inorganic PSC, which shows an impressive PCE of 14.61%, outperforming that of the Spiro-OMeTAD -based device (13.49%). Furthermore, the long-term stability of the PSC can be enhanced for YT5 compared to that of YT4 owing to the superior hydrophobicity of YT5 . These results confirm that HY5 as the HTM shows great potential for replacing Spiro-OMeTAD for application in PSCs, and also provide new important insights for further developing new HTMs with a large dimensional structure to greatly push forward the progress of PSCs.